Linguistic Awareness of the Prepositional Phrase Complexities in the English as a Foreign Language Context - Zapata-Leal, Chinger Enrique (2021)
This essay focuses on a description of the complexities of Prepositional Phrases (PPs) and their challenges for EFL learners. The rationale is to raise language awareness of the multifaceted nature of the PP in teachers and students. The grammatical explanations offered in the literature review are based on Functional Grammar. Moreover, previous research conducted addressing the issues of EFL learners facing problems with PPs are proposed in four configurations: semantic, syntactic, lexical and socio-cultural. Such configurations address scenarios for the identification of multiple meanings, different syntactic functions and structures, regional variations, typology, formal and informal language usage, among others, which represent obstacles and difficulties in the comprehension of the topic by EFL learners. Finally, we conclude that the limited use of syntactic functions, poor internal configuration of PPs, as well as the high frequency of errors reported by previous research indicate PPs are complex to use. Thereby, explicitly reinforcing the teaching of all the configurations of PPs is suggested.